Competências sintáticas no 2º ciclo do Ensino Fundamental: proposta de avaliação - Costa, Mariana de Oliveira [UNIFESP] (2017)
Purpose: To elaborate an assessment instrument of syntactic competences, to analyze their internal consistency and investigate latent factors of correlation, responsible for the variability of answers, in the different tasks that evaluate the syntactic complexity and linguistic productivity in the 4th and 5th year of the Elementary School. Methods: 113 typical schoolchildren (55.7% girls) aged from 9 to 11,1 years old (M = 9.5, SD = 0.6), regularly enrolled in 4th (N = 59.3%) and 5th (N = 40.7%) grades of Elementary School, from public school in São Paulo City. All were evaluated for auditory discrimination, auditory processing (simplified assessment), short-term and working phonological memory, expressive vocabulary and oral sentence complementation, which was elaborated with 30 main adverbial subordinate clauses (causal, consecutive, conditional, adverbial, concessive, proportional, temporal) tested for validation. Three judges evaluated the correctness and error of 3390 responses of the students. Data were analyzed by Kappa coefficient of Fleiss (= 0.6), Cronbach's Alpha coefficient (= 0.4) and factorial analysis with a Phi coefficient (= 0.7) as principal component method. Results: Judges concordance was high for items F2, F5, F6, F16, F21 and F25. The Kappa values indicated that there was no internal consistency in each adverbial category of the subordinate clauses. According to the factorial analysis, items F11, F12, F14, F15, F17, F18, F19, F28 dominated the first factor, indicating that they were correlated by the same latent factor, which accounted for 12% of the 68.1%. Conclusion: The concordance between the speech therapists judges was high, there was, the test items were not correlated within the same grammatical category and the use of the subjunctive mode in the complementary response to the main sentence seems to be a latente fator which drives the response variability of the students.